1987
DOI: 10.1007/bf00915729
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic analyses of mononuclear cells recovered from healthy and diseased human periodontal tissues

Abstract: Mononuclear cells were recovered from the gingival tissues of normal individuals and from patients with periodontal disease. Lymphocyte phenotypic markers were identified by immunofluorescence after reaction with monoclonal antibodies to T-cell subset markers. The normal tissues exhibited T4/T8 ratios almost identical to those in the peripheral blood. The diseased tissue cell ratios were significantly reduced, in both the adult periodontitis and the juvenile periodontitis groups (P less than 0.01 and P less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
71
0
2

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 34 publications
13
71
0
2
Order By: Relevance
“…T cell immune reactions to bacteria seem to play a key role in connective tissue destruction and bone resorption in PD (3). T lymphocytes are abundant in diseased periodontal tissue (4). Elevated levels of IgG Ab response to bacterial protein Ags in patients compared with healthy subjects (5) suggests a T cell association with host immune reaction to these bacteria.…”
Section: Requirement Of B7 Costimulation For Th1-mediated Inflammatormentioning
confidence: 99%
See 1 more Smart Citation
“…T cell immune reactions to bacteria seem to play a key role in connective tissue destruction and bone resorption in PD (3). T lymphocytes are abundant in diseased periodontal tissue (4). Elevated levels of IgG Ab response to bacterial protein Ags in patients compared with healthy subjects (5) suggests a T cell association with host immune reaction to these bacteria.…”
Section: Requirement Of B7 Costimulation For Th1-mediated Inflammatormentioning
confidence: 99%
“…Both G23 and F13 are CD28 ϩ /␣␤TCR ϩ and proliferate in a MHC class II-and B7-dependent manner. 4 Other characteristics of these T clones, including production of IFN-␥ and IL-2, expression of CD3, CD4, CD25, LFA-1, VLA-4, ICAM-1, and CCR5 by G23, and production of IL-4, expression of CD3, CD4, CD25, LFA-1, VLA-4, and ICAM-1 by F13, have been described previously (21,25). We considered these clones as memory cells based on the following criteria:…”
Section: T Clone Cellsmentioning
confidence: 99%
“…In terms of the transition from gingivitis to periodontitis, several studies have reported a decreased CD4/CD8 ratio (Taubman et al ., 1984a;Cole et al ., 1987;Stoufi et al ., 1987;Okada et al ., 1988;Wang et al ., 1989) in periodontal lesions, while functional studies have reported a reduced autologous mixed-lymphocyte reaction (Cole et al ., 1987). Taken together, these studies have suggested a local immunoregulatory imbalance.…”
Section: (Iv) Adaptive Immunitymentioning
confidence: 99%
“…A protective role for T cell subsets against periodontal tissue destruction has been suggested in a rat model [4], and involvement of a T cell regulatory imbalance in human chronic periodontal disease has also been demonstrated [5,6].…”
Section: Introductionmentioning
confidence: 99%